Edukasi Pemanfaatan Tanaman Obat Keluarga (Toga) Di Lingkungan Smp/Sma It Pondok Pesantren Sahabat Cendekia Pariaman - Fatridha Yansen; Eldya Mossfika; Linda Elfia (Jurnal Pengabdian Masyarakat, 2024)
Medicinal plants particularly grown by family in their own garden namely “Tanaman Obat Keluarga” (TOGA) can be used to prevent disease, promote and improve health condition and cure disease. In addition, TOGA also contributes in increasing family prosperity since medicinal plants have significant economic value. Female students known as “santriwati” who stay in Islamic boarding schools are vulnerable to diseases due to lack of hygiene and high residential density. Skin diseases, diarrhea, flu and fever are some of those diseases that students prone to be infected. Considering their conditions, which stay apart from their families, hence, independence and sufficient knowledge regarding health aspects are very necessary. This community service activity aimed to educate female students regarding the use of various types of medicinal plants (TOGA) to maintain health and treat various diseases. This socialization activity was carried out in the Islamic boarding school of the Sahabat Cendekia - Middle School/Senior High School, District of Central Pariaman, Pariaman City with 87 targeted female students. Santriwari are informed about the material related to the types of TOGA that can be planted in Islamic boarding school environments, the benefits of TOGA and how to process TOGA so that it can be used as an agent for disease prevention, health maintenance and illness treatment